Phytoestrogens from the Roots of Polygonum cuspidatum (Polygonaceae): Structure-Requirement of Hydroxyanthraquinones for Estrogenic Activity - Matsuda, H.; Shimoda, H.; Morikawa, T.; Yoshikawa, M.
The methanolic extract from the roots of Polygonum (P.)cuspidatum was found to enhance cell proliferation at 30 or 100 mg/mL in MCF-7, an estrogen-sensitive cell line. By bioassay-guided separation from P. cuspidatum with the most potent activity, emodin and emodin 8-O-b-d-glucopyranoside were isolated as active principles. The methanolic extracts from Polygonum, Cassia, Aloe, and Rheum species, which were known to contain anthraquinones, also showed the MCF-7 proliferation. As a result of the evaluation of various anthraquinones from plant sources and synthetic anthraquinones, aloe-emodin, chrysophanol, chrysophanol 8-O-b-d-glucopyranoside, and 1,8-dihydroxyanthraquinone showed weak activity. On the other hand, alizalin and 2,6- dihydroxyanthraquinone as well as emodin having the 2- and/or 6-hydoxyl groups showed potent activity. These results show that the unchelated hydroxyl group is essential for strong activity. Emodin and ,6-dihydroxyanthraquinone also inhibited 17b-estradiol binding to human estrogen receptors (ERs)with Ki values of 0.77 and 0.31 mM for ERa and 1.5 and 0.69 mM for ERb. These findings indicate that hydroxyanthraquinones such as emodin are phytoestrogens with an affinity to human estrogen receptors.